Synthesis, characterization and some properties of new soluble triarylamine-based aromatic polyamides / Azhar Kamil Rashid - Rashid, Azhar Kamil (2014)
Six new triphenylamine-containing aromatic diacid monomers, 4,4'-dicarboxy-4''-isopropyltriphenylamine, Ma, 4,4'-dicarboxy-2'4''-dimethyltriphenylamine Mb, 4,4'-dicarboxy-4''-ethyltriphenylamine, Mc, 4,4’-dicarboxy-4”-phenoxy triphenylamine, Md, 4,4'-dicarboxy-4''-(N-pyrrolyl)triphenylamine Me, 4,4',4'',4'''-(1,4-phenylene bis(azanetriyl)) tetrabenzoic acid, Mf, were successfully synthesized via the aromatic nucleophilic fluoro displacement reaction of 4-fluorobenzonitrile with aniline-derivatives using sodium hydride as the base, followed by alkaline hydrolysis of the dinitrile intermediates (Ia, Ib, Ic, Id , Ie, If). A series of poly(amine-amide)s were prepared by the direct phosphorylation polycondensation from the newly synthesized diacid monomers with various aromatic diamines. FTIR, 1H and 13C NMR spectroscopic techniques were used to identify the chemical structures of the dicyano intermediate, the carboxylic acid monomer and the resultant poly(amine-amide)s containing the triphenylamine moieties. These aromatic poly(amine-amide)s were found to be readily soluble in a variety of organic solvents and could afford strong and tough films via solution casting. They exhibited excellent thermal stability with 10% weight loss temperatures in the range of (401.2 - 577.4) °C as recorded by TGA and high glass transition temperatures between 234.5 - 292.6°C. In dilute N-methyl pyrrolidone (NMP) solution, these polymers exhibited a medium to strong UV-Vis absorption bands at the range 305 - 363 nm and photoluminescence in the blue region at 429 ~ 488 nm. Cyclic voltammetry of the poly(amine-amide)s films cast onto an ITO-coated glass substrate in dry acetonitrile (CH3CN) containing 0.1 M of tetrabutylammonium perchlorate (Bu4AlNH4ClO4) as an electrolyte exhibited one oxidation half-wave redox couples (E1/2) at 1.13 - 1.27 V vs Ag/AgCl, and revealed electrochromic characteristics with a color change from pale yellow to blue at applied potentials switched between 0.0 and 1.6 V at scan rate 0.1 V. The obtained values of the HUMO and LUMO energy levels of the currently synthesized transporting materials were in the range of 5.52 - 5.66 eV and 2.44 - 2.62 eV respectively with band gap of values of 3.04 - 3.15 eV.